ANALISIS YURIDIS PUTUSAN MAHKAMAH AGUNG RI TINGKAT PENINJAUAN KEMBALI NOMOR 1055 PK/Pdt/2022 TERKAIT SENGKETA TANAH PT PERSEBAYA DENGAN PEMERINTAH KOTA SURABAYA - Putra Pradana, Reydo Akbar; Tamsil, Tamsil (NOVUM : JURNAL HUKUM, 2022)
The land dispute between PT Persebaya and the Surabaya City Government occurred due to unlawful acts committed by the Surabaya City Government, so that PT PERSEBAYA filed a lawsuit against the Surabaya District Court. Where the judicial process for the a quo case continues up to the level of judicial review recorded in the civil case register Number 1055 PK/Pdt/2022. This research aims to determine the basis of the judge's considerations and explain the legal consequences of the decision of the Supreme Court of the Republic of Indonesia at Judicial Review level Number 1055 PK/Pdt/2022. This research is classified as normative legal research and the approaches used in this research are the statue approach, case approach and conceptual approach. The legal materials in this research consist of primary legal materials which contain statutory regulations and judge's decisions which have permanent legal force and secondary legal materials which contain legal literature related to the legal issues in this research. The technique for collecting legal materials in this research was carried out by means of a literature study of primary legal materials and secondary legal materials and data analysis techniques were carried out by providing an argument for the research results. The results of this research show that the granting of the Petition for Judicial Review on the grounds that new evidence. The results of this research show that the granting of the Petition for Judicial Review on the grounds that new evidence (novum) was found was in accordance with statutory regulations.